Lake variables - Sonde profiling from Bolmen, Subbasin West - Bolmen Research Station (Sweden Water Research, 2025)
Manual or high frequency lake profiling using sonde technology over various water depths to measure lakes of SITES Water.
Bolmen Research Station (2025). Lake variables - Sonde profiling from Bolmen, Subbasin West, 2023-10-23–2024-11-28 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/pngLWxSW7AawIqXNZGJsXwC9
Keywords: Bolmen Research Station; Chlorophyll concentration; Conductivity; Turbidity; Time instant; Time instant; Digital number of profile; Digital number of profile; Water temperature; Water temperature; Electrical conductivity; Electrical conductivity; Specific conductivity; Specific conductivity; pH; pH; Oxidation Reduction Potential; Oxidation Reduction Potential; Turbidity_FNU; Turbidity_FNU; Chlorophyll fluorescence; Chlorophyll fluorescence; Oxygen saturation; Oxygen saturation; Fluorescent dissolved organic matter; Fluorescent dissolved organic matter; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap